Word Havens: Reading One’s Way out of Trauma in Contemporary Fiction - Lucia Opreanu (University of Bucharest Review. Literary and Cultural Studies Series, 2019)
Prompted by the attention received in recent years by the collateral benefits of reading and the growing prominence of bibliotherapy in the literary marketplace, this paper aims to investigate the therapeutic effects of books as they emerge from the experience of fictional characters, a perhaps less scientifically sound endeavour than empirical studies and clinical trials targeting real-life readers but one likely to occasion interesting perspectives on reading as a coping mechanism in the face of trauma. By focusing on a variety of reading experiences gleaned from a selection of novels ranging from Mary Shelley’s Frankenstein to William Styron’s Sophie’s Choice, Graham Swift’s Waterland, Michael Ondaatje’s The English Patient, Azar Nafisi’s Reading Lolita in Tehran: A Memoir in Books, Markus Zusak’s The Book Thief, Lloyd Jones’ Mister Pip and Mary Ann Shaffer and Annie Barrows’ The Guernsey Literary and Potato Peel Pie Society and targeting acts of solitary communion with narrative as well as illicit seminars, informal book clubs and impromptu public readings, the analysis intends to highlight the extent to which literature can provide more than a mere pastime or intellectual challenge to its most vulnerable readers. Whether such benefits entail a sense of community, a temporary shelter from the hardships of war, a reprieve from the abuses of a totalitarian government or sanctuary from the less brutal but nevertheless haunting scars of broken relationships, parental disapproval or social rejection, the ultimate goal is to identify and assess the various survival strategies employed within these fictional universes.